ADMINISTRASI DAN SUPERVISI INTOLERANSI KURIKULUM BERBASIS CINTA PADA MADRASAH IBTIDAIYAH - Okta Aidil Fitri; Ananda Irene Putri; Ahmad Zainuri; Frika Farimah Zahra (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the role of administration and supervision in supporting the implementation of a love-based curriculum in Madrasah Ibtidaiyah as an effort to reduce intolerance from early education. The research uses a qualitative method with a literature study approach by analyzing various relevant written sources. The results show that administration helps teachers organize learning plans that encourage empathy and mutual respect, while supervision provides guidance for teachers to improve and strengthen teaching practices aligned with love-based values. Supporting factors include teacher commitment, availability of administrative documents, cooperation within the school, and parental involvement. Inhibiting factors include poorly structured administration, limited teacher understanding, inadequate facilities, and the lack of regular supervision. This study concludes that effective administration and supervision contribute significantly to fostering tolerant attitudes among students.